Repair Potential of Matrix-Induced Bone Marrow Aspirate Concentrate and Matrix-Induced Autologous Chondrocyte Implantation for Talar Osteochondral Repair: Patterns of Some Catabolic, Inflammatory, and Pain Mediators. (January 2017) - Desando, Giovanna; Bartolotti, Isabella; Vannini, Francesca; Cavallo, Carola; Castagnini, Francesco; Buda, Roberto; Giannini, Sandro; Mosca, Massimiliano; Mariani, Erminia; Grigolo, Brunella
Objective: The low regenerative potential of cartilage contributed to the development of different cell therapies aimed to improve the clinical outcome in young patients with Osteochondral Lesions of the Talus (OLT). This study is designed to assess the regenerative potential of autologous matrix-induced Bone Marrow Aspirate Concentrate (mBMAC) and matrix-induced Autologous Chondrocyte Implantation (mACI) evaluating, on a small number of osteochondral biopsies, the expression of some catabolic, inflammatory, and pain mediators. Design: Twenty-two patients with OLT were analyzed in this study; 7 were treated with mACI and 15 with mBMAC. Informed consent was obtained from all the patients. Clinical assessments were performed pre-operatively and at 12, 24, and 36 months after surgery using the American Orthopedic Foot and Ankle Society (AOFAS). Histology and immunohistochemistry were used to assess cartilage repair at 24 months. Data were analyzed using non-parametric Wilcoxon-Mann-Whitney and Spearman tests. Results: A remarkable improvement in AOFAS score was noticed for both treatments up to 36 months; however, patients treated with mACI reported the best AOFAS score. Various degrees of tissue remodeling were observed by histological analysis for both cell strategies. However, mBMAC treatment showed a higher expression of some fibrous and hypertrophic markers compared to mACI group. A mild positivity for nerve growth factor, as pain mediator, was noticed for both treatments.M Conclusions: Our findings demonstrated the best histological and clinical results following mACI treatment since different fibrotic and hypertrophic features were evident in the mBMAC group at 24-month follow-up.